The Influence Of Profitability And Capital Structure On Stock Returns In Food And Beverage Sub-Sector Companies Listed On The Indonesia Stock Exchange - A. Wulandari; Anwar; Abdul Rahman; Nurman; Paramaswary Aslam, Annisa (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study examines the influence of profitability and capital structure on stock returns in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research is motivated by inconsistent empirical findings in previous studies and by the phenomenon in which improvements in company profitability are not consistently followed by increases in stock returns. This condition indicates a potential gap between firm-level financial performance and market valuation, particularly in emerging market contexts. The objective of this study is to analyze both the partial and simultaneous effects of profitability, measured by Return on Equity (ROE), and capital structure, measured by the Debt to Equity Ratio (DER), on stock returns. This research employs a quantitative approach using panel data regression analysis. The sample consists of 15 food and beverage companies observed over a five-year period, resulting in 75 observations. Secondary data were obtained from published financial statements and analyzed using EViews software. Model selection was conducted through the Chow test, indicating that the Common Effect Model was the most appropriate specification. Classical assumption tests were also performed to ensure the reliability of the regression results. The empirical findings demonstrate that ROE and DER do not have a statistically significant effect on stock returns, either individually or simultaneously. The probability values of both variables exceed the 0.05 significance level, leading to the rejection of the proposed hypotheses. Furthermore, the coefficient of determination indicates that profitability and capital structure explain only a very small proportion of stock return variation. These results suggest that stock returns in the food and beverage sub-sector are more strongly influenced by external factors, such as macroeconomic conditions, inflationary pressures, investor sentiment, and overall market dynamics. The study highlights the limited explanatory power of accounting-based indicators in periods of economic uncertainty and provides important implications for investors, managers, and future research in emerging capital markets.